Corporate governance of listed companies in Thailand - Sakulrat Montreevat (Southeast Asia background series ;, 2006)
Provides an understanding of corporate governance in the context of Thailand. It explains the background and scope of corporate governance in Thailand before and after the Asian financial crisis, and details the roles of the relevant agencies and the key elements of corporate governance for listed companies.